Effect of Benzophenone-3 on performance, structure and microbial metabolism in an EGSB system. Issue 25 (9th November 2020) - Castrillón Cano, Laura; Londoño, Yudy Andrea; Pino, Nancy J.; Peñuela, Gustavo A.
ABSTRACT: Benzophenone-3 is an organic compound widely used as a UV filter, which has been reported as water pollutant and is connected with endocrine disruption in humans and animals. Expanded granular sludge beds (EGSB) are a form of an anaerobic digestion system, which has been successfully evaluated for wastewater treatment, and the removal of different compounds, however little is known about the effect of compounds as Benzophenone-3 in the performance of EGSB systems. In this study, we evaluate the effect of BP-3 on the performance, microbial structure and metabolism of EGSB reactors. For this purpose, biogas production, removal efficiencies of BP-3 and DQO were monitored. Changes in bacteria and archaea microbial structure were investigated using PCR-DGGE, and the effect on anaerobic metabolism was evaluated by measuring the expression of mcrA and ACAs genes through qRT-PCR. The systems remained stable and efficient throughout the operation stages, with CH4 percentages greater than 55% and COD and BP-3 removal percentages greater than 90%. The presence of different concentrations of Benzophenone-3 influenced the organization of microbial communities, especially archaea. However, this did not affect the stability and performance of the EGSB systems. GRAPHICAL ABSTRACT: UF0001